CHARACTERIZATION OF SHORT-LIVED INTERMEDIATES PRODUCED DURING REPLICATION OF BACULOVIRUS DNA - Mikhailov, Victor S. (2009)
In this report the short-lived DNA replication intermediates produced in both uninfected and Autographa californica multiple nucleopolyhedrovirus (AcMNPV) infected Spodoptera frugiperda cells were characterized. The methods used included pulse-labeling of DNA in permiabilized cells, treatment of nascent DNA with Mung bean nuclease, and electrophoresis in neutral and alkaline agarose gels. In contrast to uninfected cells that produced a population of small DNA fragments of about 200 bp, a population of heterogeneous fragments of up to 5 kb with an average size of 1 to 2 kb derived randomly from the virus genome was identified as the short-lived intermediates produced during AcMNPV replication. The intermediates likely include Okazaki fragments derived from the lagging strands in viral replication forks as well as fragments produced during the recombination-dependent replication.